Effects of the fuel blend flow rate on engine combustion performance - Onojowho, E. E.; Asere, A. A. (Frontiers in Energy Research, 2024)
The aim of this study is to investigate the post-injection flow interactive effects of atomized fuel blends from an injector system of known characteristics into a direct injection compression ignition engine combustion chamber and their outcomes. Attempts were made to link the interactive influence of blend mixture quality, effluence and consumption rate of fuel injection properties on frictional loss, heat liberation, combustion, and volumetric efficiency performance outcomes of the engine. This numerical–experimental dimension study began with computational fluid dynamics (CFD) prediction of fuel in-cylinder behavior between a 225° CA (crank angle) (45°ABDC—after bottom dead center) and 360°CA (0° BTDC—before top dead center) compression stroke elapsing into an expansion stroke. A Testo gas analyzer was used to determine the combustion efficiency. The experiments validated the CFD outcomes presented. Willans lines were applied on blends to compare piston frictional losses. A swirl prediction maximum peak of 0.027237 at 336.15 CA for pure diesel blend (D100) at 2,300 rpm and 0.066811 at 341.3 CA for pure biodiesel blend (B100) at 1,800 rpm aided the mixing quality. The instantaneous velocity on the sinusoidal profile and contour around the swirling peak crank angle revealed ignition activity resulting from high mixing quality. The engine possessed high-efficient fuel blends burning strength on a minimum of 54.5% at a higher flow rate. The engine speed and flow rate interaction on the heat liberation rate made a symmetric profile for D100 and B100. Engine energy loss on friction was minimal with D100 compared to B100 and 5% biodiesel to 95% diesel blend (B5).
Keywords: fuel flow rate; piston frictional losses; engine heat liberation rate; combustion efficiency; internal combustion engine numerical effluence